Emanuel Celler papers - Celler, Emanuel, 1888-1981.
Correspondence, memoranda, speeches, notes, financial records, clippings, printed matter, and other papers relating chiefly to Celler's service as a U.S. representative from New York State and as chairman of the House Committee on the Judiciary. Documents Celler's work as chairman of Subcommittee No. 5 (Subcommittee on Study of Monopoly Power) of the Committee on the Judiciary including the investigation into the exemption of professional baseball from antitrust laws. Includes files of the New York congressional delegation steering committee. Subjects include American Jewish issues, eastern Nigeria (Biafra), busing, Cambodia, campus disorders, civil rights, crime, foreign trade, the proposed impeachment of William O. Douglas, immigration, India, internal security and loyalty, Israel and Zionism, Pat McCarran and the Immigration and Nationality Act of 1952 (McCarran-Walter Act), Joseph McCarthy, mergers in the banking and communications industries, monopolies, mutual security, oil, oligopoly, pollution, poverty, Adam Clayton Powell, presidential disability, refugees, religion in schools, segregation, selective service, sports, U.S. House Committee on Un-American Activities, trusts, Vietnam, and welfare.
Correspondents include Dean Acheson, Alben William Barkley, David Ben-Gurion, Chester Bowles, Harry Flood Byrd, Maurice Couve de Murville, William O. Douglas, Cyrus Stephen Eaton, Abba Solomon Eban, Levi Eshkol, James T. Farrell, Abe Fortas, W. Averell Harriman, J. Edgar Hoover, Harry L. Hopkins, Cordell Hull, Hubert H. Humphrey, Harold L. Ickes, Lyndon B. Johnson, Estes Kefauver, George F. Kennan, William F. Knowland, Teddy Kollek, Fiorello H. LaGuardia, Owen Lattimore, John V. Lindsay, John McCormack, George S. McGovern, Wilbur D. Mills, Jawaharlal Nehru, Richard M. Nixon, Vijaya Lakshmi Pandit, David de Sola Pool, Hyman George Rickover, Nelson A. Rockefeller, Franklin D. Roosevelt, Jr., Frank Stanton, Adlai E. Stevenson, Henry L. Stimson, Robert A. Taft, Norman Thomas, Harry S. Truman, Robert F. Wagner, Henry A. Wallace, and Roy Wilkins.
Microfilm edition of containers 14-19 of the Subject File available
Microfilm edition produced from originals in the Manuscript Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Lawyer and U.S. representative from New York.
Collection material in English.
Keywords: Acheson, Dean, -- 1893-1971 -- Correspondence; Barkley, Alben William, -- 1877-1956 -- Correspondence; Ben-Gurion, David, -- 1886-1973 -- Correspondence; Bowles, Chester, -- 1901-1986 -- Correspondence; Byrd, Harry F. -- 1887-1966 -- Correspondence; Couve de Murville, Maurice, -- 1907-1999 -- Correspondence; Douglas, William O. -- 1898-1980.; Douglas, William O. -- 1898-1980 -- Correspondence; Eaton, Cyrus Stephen, -- 1883-1979 -- Correspondence; Eban, Abba Solomon, -- 1915-2002 -- Correspondence; Eshkol, Levi, -- 1895-1969 -- Correspondence; Farrell, James T. -- 1904-1979 -- Correspondence; Fortas, Abe -- Correspondence; Harriman, W. Averell -- 1891-1986 -- Correspondence; Hoover, J. Edgar -- 1895-1972 -- Correspondence; Hopkins, Harry L. -- 1890-1946 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kefauver, Estes, -- 1903-1963 -- Correspondence; Kennan, George F. -- 1904-2005 -- Correspondence; Knowland, William F. -- 1908-1974 -- Correspondence; Kollek, Teddy, -- 1911-2007 -- Correspondence; La Guardia, Fiorello H. -- 1882-1947 -- Correspondence; Lattimore, Owen, -- 1900-1989 -- Correspondence; Lindsay, John V. -- Correspondence; McCarran, Pat, -- 1876-1954.; McCarthy, Joseph, -- 1908-1957.; McCormack, John W., -- 1891-1980 -- Correspondence; McGovern, George S. -- 1922-2012 -- Correspondence; Mills, Wilbur D. -- 1909- -- Correspondence; Nehru, Jawaharlal, -- 1889-1964. -- Correspondence; Nixon, Richard M. -- 1913-1994 -- Correspondence; Pandit, Vijaya Lakshmi, -- 1900-1990 -- Correspondence; Pool, David de Sola, -- 1885-1970 -- Correspondence; Powell, Adam Clayton, -- 1908-1972.; Rickover, Hyman George -- Correspondence; Rockefeller, Nelson A. -- 1908-1979.; Roosevelt, Franklin D. -- 1914-1988.; Stanton, Frank, -- 1908-2006 -- Correspondence; Stevenson, Adlai E. -- 1900-1965 -- Correspondence; Stimson, Henry L. -- 1867-1950.; Taft, Robert A. -- 1889-1953.; Thomas, Norman, -- 1884-1968 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Wagner, Robert F. -- 1877-1953 -- Correspondence; Wallace, Henry A. -- 1888-1965 -- Correspondence; Wilkins, Roy, -- 1901-1981 -- Correspondence; United States. -- Congress. -- House; United States. -- Congress. -- House. -- Committee on the Judiciary; United States. -- Congress. -- House. -- Committee on the Judiciary. -- Subcommittee No. 5.; United States. -- Congress. -- House. -- Committee on Un-American Activities; United States; Banks and banking -- United States; Baseball -- United States; Busing for school integration -- United States; Civil rights -- United States; Communication and traffic -- United States; Crime -- United States